Hidden Identities Shape Student Perceptions of Active Learning Environments - Henning, Jeremiah A.; Ballen, Cissy J.; Molina, Sergio A.; Cotner, Sehoya (Frontiers in Education, 2019)
Active-learning pedagogies represent one suite of tools commonly thought to promote greater classroom inclusivity. However, the social aspects of many active-learning techniques, such as in-class group work, may differentially impact students who feel pressure to conceal certain aspects of their identity, such as sexual orientation, political affiliation, or religion. We used a post-course survey of over 1300 students at a large midwestern University to ascertain which aspects of a student’s identity are most salient in their experiences in active-learning environments, especially with respect to group work. Using path analysis, we show that students who are politically conservative, religious, or who commute to campus perceive lower inclusion in active-learning environments, while students who identify as queer report negative experiences in groups. These and other findings lead us to conclude that targeted efforts to improve classroom climate, such as equitable teaching strategies, will benefit students who might feel marginalized in peer-learning environments.